GENDER DIVERGENCE IN ENGLISH LEARNING MOTIVATION AT THE TENTH GRADE STUDENTS OF KARTIKATAMA SENIOR HIGH SCHOOL METRO - Rizky Amalia; Deri Sis Nanda (LINGUISTIKA, 2017)
English subject aims to enable students to have good communication skill in this globalization era. Indonesian people learn this international language since they are in elementary school to senior high school. Although they have studied for 12 years, they cannot master English. One of the factors makes them fail in achieving the competence in learning English is “motivation”. There are two types of motivation; those are instrumental and integrative motivation. Furthermore, there is the different motivation between male and female students in learning English. This research investigated the gender divergence on English learning motivation of the tenth grade students of Kartikatama Senior High School whether they are motivated instrumentally or integratively and which one is highly motivated between male and female students. The descriptive quantitative data were applied in this research. The questionnaires distributed to 70 students at grade 10. The questionnaire instrument was adopted from a modified version of Gardner’s AMTB (Attitude/ Motivation Test Battery) in 1985. It consisted 14 items which used 5 point Likert Scale ranging from ‘strongly agree’ to ‘strongly disagree’. The result of the questionnaire was calculated by using Microsoft Excel version 2007. The measurement result continued by categorizing the score of each items by using Arikunto’s formula “HIGH” and “LOW to know the motivation of the students in each items. The results of the research are; male students of the tenth grade students of Kartikatama Senior High School have higher motivation than female students and both male and female students were instrumentally motivated toward learning English.